2021
DOI: 10.3390/app11146479
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Veracity on the Load Monitoring of Professional Soccer Players: A Systematic Review in the Face of the Big Data Era

Abstract: Big Data has real value when the veracity of the collected data has been previously identified. However, data veracity for load monitoring in professional soccer players has not been analyzed yet. This systematic review aims to evaluate the current evidence from the scientific literature related to data veracity for load monitoring in professional soccer. Systematic searches through the PubMed, Scopus, and Web of Science databases were conducted for reports onthe data veracity of diverse load monitoring tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…The addition of veracity metrics related to physical testing and workload monitoring could also help. A recent paper reported that data veracity (accuracy, reliability, and quality of data) was found for 54% of tools and 23% of the parameters used in testing and workload monitoring in soccer studies [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of veracity metrics related to physical testing and workload monitoring could also help. A recent paper reported that data veracity (accuracy, reliability, and quality of data) was found for 54% of tools and 23% of the parameters used in testing and workload monitoring in soccer studies [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, technological evolution allows to easily monitor players' performance permitting to create large data set that warrants to have a complete overview of the players' status (30). In this way, a huge quantity of tools and indicators are now developed to evaluate loads in elite professional soccer (30). Actually, experts have highlighted that to date no single measure can accurately quantify the fitness and fatigue responses to training stimuli, but they encourage the use of both external and internal load (IL) index as information that describe training-load adaptation (23).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there is evidence from several sports that if load is used in a moderate and progressive approach, avoiding rapid fluctuations (i.e., increases or decreases) could be protective against noncontact injuries (80). In recent years, technological evolution allows to easily monitor players' performance permitting to create large data set that warrants to have a complete overview of the players' status (30). In this way, a huge quantity of tools and indicators are now developed to evaluate loads in elite professional soccer (30).…”
Section: Introductionmentioning
confidence: 99%
“…Within this topic, multiple articles have been published researching risk factors of these injuries and the effectiveness of injury prevention programmes 5 6. As sport injuries are mostly a consequence of complex interactions of multiple risk factors,7 plenty of data has already been collected—with the objective of injury prevention8 Some examples of the most used and reliable data collection methods for load monitoring in football are: electronic performance tracking system (distance, speed, accelerations,…), physiological monitoring (maximal heart rate, heart rate variability, etc), force plate testing (jump height, power output, etc), blood sampling (cortisol, testosterone, etc), questionnaires (wellness, rate of perceived exertion, etc) and tensiomyography (muscle contraction time, etc) 9. In this abundance of data, many applications of artificial intelligence (AI) and machine learning (ML) are relevant to sports practitioners in this domain 10…”
Section: Introductionmentioning
confidence: 99%